SEX AND ENDURANCE PERFORMANCE - Martin Pupiš; Aleksandar Raković; Danijel Stanković; Miodrag Kocić; Vladimir Savanović (Sport Scientific And Practical Aspects, 2025)
This work clarifies problems of the perception of sexual activity by long-distance athletes before physical loading. The group that answered a questionnaire comprised 62 race-walkers and long-distance runners from 6 European countries age of 32 years ± 8 years. Questionnaire was composed of 8 closed questions with extra questions. More than 90% of addressed athletes suppose that having a sex 12 hours before endurance performance does not influence it. Immediately after sexual intercourse 40% of athletes have worse feelings during intensive loading. At the aerobic loading it does not change subjects’ feelings or heart rate.Unambiguously we cannot say that having sex before physical loading influences performance positively or negatively.